Recreation: A Panacea for Youths Restiveness in the Niger Delta Region of Nigeria - Muhammad, Sanusi Abdul (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The Niger Delta struggle is at the root of most of our national discomfort. Urgent steps should be taken in order to improve the standard of living of people of the Niger Delta region. If not they would continue to be restive and dependent on what they cannot get through illegal means. The initiative of the federal government to give the people a sense of belonging by setting up the Niger Delta Ministry is commendable, and it is hope that if the objective is faithfully implemented, and youths engage in recreation activities it will go a long way in curbing youth’s restiveness in the region. The communities believe the oil companies who engage in explorations on their land and water have paid negligible attention to their problems. This paper therefore, highlights oil mineral producing areas development commission, concept of recreation, rationale for recreational pursuits and importance of recreation in curbing youth’s restiveness. It concluded that youths spend their leisure in unwholesome activities, and recommended provision of recreation facilities, supervision of recreation facilities and equipment, and employment of recreation experts for effective management of the programmes and facilities among others.